2017
DOI: 10.1002/mus.25712
|View full text |Cite
|
Sign up to set email alerts
|

Improving symptom management for people with amyotrophic lateral sclerosis

Abstract: Introduction Symptomatic management is the main focus of ALS clinical care. We aim to report the prevalence of ALS‐related symptoms and characterize self‐reported symptomatic management. Methods A symptom management survey developed by the Muscular Dystrophy Association Clinical Research Network was completed by ALS registrants. Logistic regression identified potential predictors of symptom prevalence, severity, and treatment. Results A total of 567 ALS participants reported fatigue (90%), muscle stiffness (84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Pain appears to continue to be an uncontrolled symptom for many PALS, in keeping with prior studies suggesting this is an under recognized and undertreated symptom (24)(25)(26). Fatigue was also noted by a large percentage of caregivers and PALS and available treatments for this symptom are limited and of unclear efficacy (27,28). Quality of life assessment instruments exist which incorporate evaluation of these diverse, impactful symptoms (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain appears to continue to be an uncontrolled symptom for many PALS, in keeping with prior studies suggesting this is an under recognized and undertreated symptom (24)(25)(26). Fatigue was also noted by a large percentage of caregivers and PALS and available treatments for this symptom are limited and of unclear efficacy (27,28). Quality of life assessment instruments exist which incorporate evaluation of these diverse, impactful symptoms (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Depression and cognitive changes were also frequently noted by both PALS and caregivers. Increased attention to these symptoms in research studies and in our clinics is warranted, and has been recommended in other recent work (28,34).…”
Section: Discussionmentioning
confidence: 99%
“…The constant impairment was fatigue, without any variation throughout the study [ 23 ]. A survey study by Nicholson et al (2018) reported that fatigue was the most prevalent and untreated symptom in ALS patients [ 57 ]. These results are in contrast with ours, mainly due to the method used.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation in line with findings that patients with ALS experience fatigue as use-dependent reversible muscle weakness and whole-body tiredness [ 34 ]. A recent survey-study in patients with ALS report that fatigue is the most prevalent impairment and at the same time the least treated [ 35 ]. There is, unfortunately, not enough evidence to make conclusions about effectiveness of pharmacological or non-pharmacological treatments [ 36 ].…”
Section: Discussionmentioning
confidence: 99%